The Influence of Semiotic Advertising Efficacy on Gen-Y Purchase Intent of Smart Phone - Elizabeth Adaobi Oputa; Fakhrorazi Ahmad (AIBPM Publisher, 2018)
The paper presents an empirical analysis to demonstrate the influence of semiotic advertising efficacy on generation-y purchase intent of smart phone. Semiotic advertising is an effective, modern approach to advertising that focuses on the use of different signs, symbols, images and other visual aids for the purpose of marketing a given product or service. Since these signs tend to create an image of the brand in minds of consumers and also demonstrates the brand association with their cultural orientation, beliefs and values, semiotic advertising is said to have a significant impact on the brand equity as perceived by generation y customers. The study also confirms that since higher brand equity based on its components of perception, recognition, parity, loyalty and trust influences the purchase intentions and decisions of generation-y smart phone users positively, semiotic advertising must also have a positive influence on the purchase intent of the buyers. The study has thus been based on the responses received from 620 generation-y smart phone users from a survey based on an instrument developed by the researcher to measure semiotic advertising efficacy, brand equity and purchase intentions as perceived towards advertisements of four smart phones shown to the respondents while undertaking the survey. The data obtained from the questions based on Likert scales has been analysed to prove the hypotheses as derived in the study. Outcomes as based on statistical path analysis establish that overall equity of a brand as perceived by generation y customers, increases with an increase in semiotic advertising efficacy and also the perceived brand equity has a positive and direct influence on purchase intentions. It is hence concluded from the discussions and findings that the purchase intentions of generation y smart phone users increase when the efficacy of semiotic advertising increases. The brands can be recommended to thus make sure that the visual elements and semiotics used in their advertisements align with cultural characteristics of buyers to enhance their overall efficacy.